Tanggung Jawab Hukum Notaris terhadap Keabsahan Akta Pendirian Koperasi Berdasarkan Undang-Undang Nomor 6 Tahun 2023 tentang Cipta Kerja - Sonia Desi Lestari (Jurnal Hukum Lex Generalis, 2026)
This study aims to examine how the regulations for the establishment of cooperatives after the enactment of Law Number 6 of 2023 concerning Job Creation, as well as the limits of Notary's responsibility regarding the validity of the cooperative's deed of establishment if a legal flaw occurs in the establishment process. This type of research is normative legal research using a statutory approach (Statute approach), a conceptual approach (Conceptual approach) and a case approach (Case approach). The results of this study indicate that the regulations for the establishment of cooperatives after the enactment of Law Number 6 of 2023 concerning Job Creation indicate a new paradigm, namely from a rigid administrative approach to a more flexible and business-based approach.